2003
DOI: 10.4319/lo.2003.48.6.2377
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of phytoplankton and other particles to inherent optical properties in New England continental shelf waters

Abstract: Variability in upper ocean optical properties is often driven by changes in the particle pool. We investigated the effects of such changes by characterizing individual particles. For particles in natural assemblages, we used a combination of Mie theory and flow cytometry to determine diameter (D), complex refractive index (n ϩ inЈ), and optical cross-sections at 488 nm. Particles were grouped into categories of eukaryotic pico/nanophytoplankton, Synechococcus, heterotrophic prokaryotes, detritus, and minerals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 62 publications
5
72
1
Order By: Relevance
“…5). These findings add to previous studies that have 1) demonstrated in the laboratory that the carbonspecific scattering cross-section of different phytoplankton groups grown under different conditions is rather constrained (Stramski and Morel, 1990;Stramski and Reynolds, 1993;DuRand et al, 2002); 2) suggested that c p can track phytoplankton biomass (Durand and Olson, 1996;Chung et al, 1996Chung et al, , 1998Green et al, 2003;Oubelkheir et al, 2005); 3) shown that chl-a:c p ratios are closely correlated to variations in phytoplankton physiological parameters in the field (Behrenfeld and Boss, 2003); 4) demonstrated that the ratio of chl-a to a function of b bp retrieved from ocean color data tracks physiological trends expected from laboratory experiments over vast oceanic regions ; and 5) shown that the seasonal cycles of satellite-based chla:b bp follow closely, in the oligotrophic ocean, those of the in-situ cellular fluorescence of Prochlorococcus (Westberry et al, 2008). Together, these different lines of evidence add support to the hypothesis that b bp can provide an alternative to chl-a for monitoring open-ocean phytoplankton biomass from space Westberry et al, 2008).…”
Section: Final Remarkssupporting
confidence: 83%
See 4 more Smart Citations
“…5). These findings add to previous studies that have 1) demonstrated in the laboratory that the carbonspecific scattering cross-section of different phytoplankton groups grown under different conditions is rather constrained (Stramski and Morel, 1990;Stramski and Reynolds, 1993;DuRand et al, 2002); 2) suggested that c p can track phytoplankton biomass (Durand and Olson, 1996;Chung et al, 1996Chung et al, , 1998Green et al, 2003;Oubelkheir et al, 2005); 3) shown that chl-a:c p ratios are closely correlated to variations in phytoplankton physiological parameters in the field (Behrenfeld and Boss, 2003); 4) demonstrated that the ratio of chl-a to a function of b bp retrieved from ocean color data tracks physiological trends expected from laboratory experiments over vast oceanic regions ; and 5) shown that the seasonal cycles of satellite-based chla:b bp follow closely, in the oligotrophic ocean, those of the in-situ cellular fluorescence of Prochlorococcus (Westberry et al, 2008). Together, these different lines of evidence add support to the hypothesis that b bp can provide an alternative to chl-a for monitoring open-ocean phytoplankton biomass from space Westberry et al, 2008).…”
Section: Final Remarkssupporting
confidence: 83%
“…A validation of the above estimates was only presented by Green et al (2003) who favorably compared the reconstructed total particulate scattering signals to independently measured bulk b p (which dominates c p ). Indeed, most of the aforementioned investigations adopted different hypotheses to which the calculated scattering cross-sections are strongly dependent: for example, some studies employed forward scattering measurements to obtain particle sizes (Durand and Olson, 1996;Chung et al, 1998;Green et al, 2003;Grob et al, 2007), while others assumed fixed sizes for a given particle type (Chung et al, 1996;Claustre et al, 1999;Oubelkheir et al, 2005).…”
Section: G Dall'olmo Et Al: Particulate Backscattering In the Oceanmentioning
confidence: 99%
See 3 more Smart Citations